Die jungquartäre morphologische Entwicklung des Saartales - Zandstra, K. J. (ERDKUNDE, 1954)
1. Of the most recent river deposits which have here been termed „Auelehm“ (haugh-loam), sandyloamy levees and loamy-clayey basins may be distinguished. 2. The gravel fans of periglacial tributary valleys, situated at their junction with the main valley, are on the whole younger than the major part of the haugh-loam. 3. The deposition of haugh-loam can thus be considered a consequence of human conditioned soil erosion. 4. Beneath the layer of haugh-loam is found an undulating gravel surface into which wide river branches were deepened during the Atlantic period and later. 5. Following Mensching’s example the niederterrasse(low terrace) may in the Saar area also be subdivided into an upper and a lower section (O. N. T. and U. N. T. respectively). 6. On the basis of palynological, palaeontological, stratigraphical, pedological and morphological data it was possible to prove the extreme periglacial character of the upper section of the low terrace (O. N. T.). 7. The swampy meadow of Saarbrücken and the semicircular haugh south-west of Saarlouis can be interpreted as river basins which date from the climax of periglacial conditions. Later, wide flood water channels were deepened into these river beds. The silting up of these channels began during the Boreal period. 8. During the Alleriod period the river Saar not only removed part of the upper low terrace but in addition cut several metres deep into the solid rock. 9. The lower section of the low terrace (U. N. T.) was deposited during the cold younger Dryas period, Late Glacial III. At the turn from Late-Glacial to Post-Glacial in a phase of degradation which, though with rapidly decreasing effect, lasted until the Atlantic period, this lower terrace section (U. N. T.) was largely reduced. 10. It is suggested that the Saar terraces should be classified into four groups which may possibly run parallel to the four glacial periods as described by A. Penck and Brückner. In the paper the typical characteristics of each group of terraces are discussed briefly.